Pengaruh Gaya Belajar Visual, Auditori, dan Kinestetik terhadap Hasil Belajar Bahasa Arab Siswa Di SMP Yayasan Perguruan Istiqomah Islamic Fullday School - Leoni Wilyam; Yahfizham (Yayasan Bayt Shufiya Nusantara, 2025)
This study aims to determine the effect of visual, auditory, and kinesthetic learning styles on Arabic learning outcomes of junior high school students. This study uses a quantitative approach with a survey method. Data were collected through distributing questionnaires to 60 junior high school students selected by purposive sampling. Data analysis was conducted using multiple linear regression to see the contribution of each learning style to Arabic learning outcomes. The results showed that visual, auditory, and kinesthetic learning styles simultaneously had a positive and significant effect on students' Arabic learning outcomes. Among the three learning styles, visual learning style has the most dominant influence on students' Arabic learning outcomes. Based on these results, it is concluded that the diversity of students' learning styles needs to be considered in the learning process, especially in learning Arabic. Teachers are expected to use a variety of learning methods that are in accordance with students' learning styles so that learning becomes more effective and student learning outcomes increase.